Impact of the Covid-19 Pandemic on Indonesia Halal Tourism Transportation - Peristiwo, Hadi (Journal of Digital Marketing and Halal Industry, 2021)
The covid 19 pandemics have slowed down the world economy, especially Indonesia, especially in the halal tourism sector. As known halal tourism sector is hard hit by the pandemic covid 19, especially in the transport sector which is much in the set on the restriction of physical distance. This journal's literature review will explore the impact of covid-19 on the role of the transportation sector in the halal tourism industry in Indonesia, as well as identify opportunities and challenges in the transportation sector for halal tourism during the Covid-19 pandemic. This journal review literature research method is carried out by searching for published articles on Sage, Elsevier Science, and Taylor Francis with the selected keywords namely Covid-19, Transportation, and Halal Tourism. The search was carried out by limiting publications from 2010–2020. From the results of the literature search, it can be seen that there was a change or shift in behavior from pre-covid-19 activities to the covid-19 era which had a direct impact on decreasing the movement or mobility of the Indonesian population in the halal tourism transportation sector. Transportation with a health element as the main requirement that needs to be implemented in halal tourism is an important aspect for sustainable halal tourism during the covid-19 pandemic.